Self-determination theory in physical education: A systematic review of qualitative studies. (March 2021) - White, Rhiannon Lee; Bennie, Andrew; Vasconcellos, Diego; Cinelli, Renata; Hilland, Toni; Owen, Katherine B.; Lonsdale, Chris
Abstract: This review examined qualitative evidence of self-determination theory tenets within physical education. We conducted systematic searches in four databases, included 34 studies, and thematically analysed data from all included studies. Results indicated that certain teaching strategies provided students with the opportunity to undermine other students' relatedness. Low relatedness and competence satisfaction were associated with negative affect and reduced participation, meaning teacher behaviours that undermined competence and enabled peer teasing were counterproductive to the purpose of physical education. Need satisfaction, however, was associated with positive affect and increased participation. Therefore, teaching in line with self-determination theory may improve student outcomes. Highlights: Novelty, choices, and challenges satisfy needs and enhance intrinsic motivation. Teacher focus on performance thwarts competence and promotes amotivation. Some teacher behaviours encourage students to undermine each other's' needs. Peer comparisons and peer teasing highlight incompetence and thwart relatedness. Positive peer relationships promote relatedness satisfaction and positive affect.